2015
DOI: 10.1002/jpln.201400261
|View full text |Cite
|
Sign up to set email alerts
|

Recovery efficiency of nitrogen from liquid and solid fractions of pig slurry obtained using different separation technologies

Abstract: The characteristics of solid (SF) and liquid (LF) fractions resulting from solid–liquid separation of pig slurry depend on the separation technique used. It can be assumed that the separation technique will also affect the nitrogen (N) availability to plants. A pot experiment was performed with ryegrass to compare the N‐recovery efficiency of SFs and LFs obtained with four frequently used separation techniques (centrifugation [Cent], sediment settling during 20 h [Sed], enhanced settling during 20 h by additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
1
0
0
2
Order By: Relevance
“…Therefore, we found that organic fertilization carries a higher risk of N leaching than chemical fertilization, which is consistent with some earlier findings [46,47], despite more research having widely shown that the application of organic N fertilizer would cause a decrease in N leaching than inorganic [48][49][50]. Most of the nitrogen in organic fertilizer exists in the form of macromolecular, which can only be absorbed by plants after a certain period of dissolution by a series of microbial-mediated steps [51,52]. Therefore, compared with inorganic nitrogen from chemical N, it is difficult to be directly used by crops.…”
Section: N Leachingsupporting
confidence: 91%
“…Therefore, we found that organic fertilization carries a higher risk of N leaching than chemical fertilization, which is consistent with some earlier findings [46,47], despite more research having widely shown that the application of organic N fertilizer would cause a decrease in N leaching than inorganic [48][49][50]. Most of the nitrogen in organic fertilizer exists in the form of macromolecular, which can only be absorbed by plants after a certain period of dissolution by a series of microbial-mediated steps [51,52]. Therefore, compared with inorganic nitrogen from chemical N, it is difficult to be directly used by crops.…”
Section: N Leachingsupporting
confidence: 91%
“…In onderstaande tabellen worden de resultaten van het literatuuronderzoek samengevat voor rundveeen varkensdrijfmest, voor zover deze voldeden aan de in paragraaf 2.2 genoemde 3 criteria. De resultaten van literatuurbronnen die niet voldeden aan een of meerdere criteria (Fangueiro et al, 2015; een aantal metingen uit Derikx, 2019;Gastel et al, 1997;Lemmens et al, 2007;Rexilius, 1990;Schön et al, 1989;Vu et al, 2016) zijn niet opgenomen in Tabel 5 en 6 en worden niet nader gebruikt.…”
Section: Literatuuronderzoekunclassified
“…De resultaten van literatuurbronnen die niet voldeden aan een of meerdere criteria (Fangueiro et al, 2015;Gastel et al, 1997;Lemmens et al, 2007;Rexilius, 1990;Schön et al, 1989;Vu et al, 2016) zijn niet opgenomen in Tabel 5 en 6 en worden niet nader gebruikt.…”
Section: Literatuuronderzoekunclassified